Image-based pornography detection - Ap-Apid, Rigan P. (Animo Repository, 2008)
This paper presents an algorithm for detecting pornography or nudity in color images based on a skin color distribution model. The skin color model is based on correlation analyses of RGB and HSV color components. This model is used to identify and locate skin regions in an image. The skin regions are analyzed for clues indicating nudity or non-nudity such as their sizes and relative distances from each other. The Nudity Detection Algorithm is able to detect nudity with a 94.85% recall and a false positive rate of 6.52% on a set of images consisting of 641 nude images and 936 non-nude images.